2009
DOI: 10.4049/jimmunol.0803366
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Aβ-Displaying Virus-Like Particles Reduces Soluble and Insoluble Cerebral Aβ and Lowers Plaque Burden in APP Transgenic Mice

Abstract: In transgenic animal models, humoral immunity directed against the β-amyloid peptide (Aβ), which is deposited in the brains of AD patients, can reduce Aβ plaques and restore memory. However, initial clinical trials using active immunization with Aβ1–42 (plus adjuvant) had to be stopped as a subset of patients developed meningoencephalitis, likely due to cytotoxic T cell reactions against Aβ. Previously, we demonstrated that retrovirus-like particles displaying on their surface repetitive arrays of self and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…Based on previous work we decided to use the platelet-derived growth factor receptor (PDGFR) transmembrane domain, which becomes efficiently incorporated into retrovirus particles and can be fused to proteins or peptides of choice (34,35). Fusion of the reading frame of the Her2/neuspecific DARPin 9.29 (27) to the PDGFR transmembrane domain resulted in the construct pDisplay-D 9.29 (Fig.…”
Section: Separating Receptor Attachment From H Proteinmentioning
confidence: 99%
“…Based on previous work we decided to use the platelet-derived growth factor receptor (PDGFR) transmembrane domain, which becomes efficiently incorporated into retrovirus particles and can be fused to proteins or peptides of choice (34,35). Fusion of the reading frame of the Her2/neuspecific DARPin 9.29 (27) to the PDGFR transmembrane domain resulted in the construct pDisplay-D 9.29 (Fig.…”
Section: Separating Receptor Attachment From H Proteinmentioning
confidence: 99%
“…47 In 2009, using engineered MLV retroparticle VLPs displaying Ab 1-15 , Bach and colleagues showed that a single dose of vaccine without adjuvant elicited high titers of anti-Ab antibodies in APP mice. 48 Immunization resulted in a statistically significant ∼40% reduction in plaque area and number in the brain as compared to nonvaccinated control mice. Recently, we showed that immunization with Qb bacteriophage VLPs conjugated with peptides representing Ab 1-9 or Ab 28-40 resulted in hightiter antibody responses and significant reductions (40-70% depending on the assay) of Ab deposition in the brains of APP mice.…”
Section: Vlps As Platforms For Antigenic Displaymentioning
confidence: 95%
“…53 Accordingly, immunization with HPV, Qb bacteriophage and MLV VLPs displaying short (9-16 amino acid) peptides derived from the N-terminus of Ab does not induce T-cell proliferative responses against Ab. 48,53 Efficacy of VLP-based vaccines in the APP mouse model. Three studies have examined the effectiveness of vaccination with VLP-based immunogen targeting Ab in various APP mouse models.…”
Section: Vlps As Platforms For Antigenic Displaymentioning
confidence: 99%
See 1 more Smart Citation
“…When 1 × 10 10 particles were injected intravenously in APP23 mice, they produced high titers of anti-Aβ antibodies, and the subtypes were IgG1 and IgG2b. The immunized mice showed significant reduction of SPs, soluble and insoluble Aβ (Bach et al 2009). Each virus-like particle expresses several thousands epitopes of A β 1-15 and the injected particles were calculated as containing 150 ng of Aβ 1-15.…”
Section: Murine Leukemia Virus (Mlv) Particles Expressing Aβ 1-15 Pepmentioning
confidence: 99%